(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2017)
تركزت الدراسة في هذا البحث على تحديد نزر بعض العناصر المعدنية الثقيلة (النحاس Cu، الكادميوم Cd، الرصاص Pb) في بعض أنواع الطحالب البحرية المنتشرة على شاطئ مدينة بانياس خلال عام 2014 وذلك باستخدام مطيافية الامتصاص الذري (تقانة اللهب Flame-AAS). تشير النتائج إلى ارتباط تغير تراكيز كل من الرصاص، الكادميوم والنحاس بنوع الطحلب ومواقع جمع العينات من جهة، وبمصادر التلوث من جهة أخرى، لوحظ أن النوعين Sargassum vulgare (طحلب أسمر) والـ Enteromorpha linza (طحلب أخضر) أكثر مراكمة للعناصر الثقيلة من الأنواع الأخرى وخاصة أنواع الطحالب الحمراء. تراوحت تراكيز عنصر النحاس بين 1.291ppm و 11.716ppm في الأنواع المدروسة، حيث بلغت أعلى قيمة في طحلب الـ Enteromorpha linza وأدناها في طحلب الـSargassum vulgare، أما بالنسبة لعنصر الرصاص كانت أعلى قيمة (59.354 ppm) في طحلب الـ Enteromorpha linza وأدنى قيمة (6.46 ppm) في طحلب الـ Ulva fasciata، بينما سجلت أعلى القيم لعنصر الكادميوم (10.457ppm) في طحلب الـ Enteromorpha linza وأدناها (0.666 ppm) في طحلب الـUlva fasciata. The study focused in this research to determine the trace of some heavy metal elements (Copper Cu, Cadmium Cd, Lead Pb) in some types of marine macroalgae scattered on the shore of the city of Banias during 2014, using atomic absorption spectroscopy (technology flame Flame- AAS). The results indicate that the concentrationsofeach of Copper, Cadmium and Lead have a link with macroalgae types, sampling sites from direction, and Source of pollution on the other hand; it was observed that the accumulation of heavy metals in both of Sargassum vulgare (browen algae) and Enteromorpha linza (green algae) was more than red algae. Copper concentration ranged between 1.291 ppm and 11.716 ppm in the studied species, Reaching the highest value in the Enteromorpha linzaalgae and the lowest in Sargassum vulgarealgae, the highest value of Lead element was (59.354 ppm) in Enteromorpha linzaand the lowest value of it was (6.46 ppm) in Ulva fasciata, While the highest values of the element Cadmium recorded (10.457 ppm) in Enteromorpha linza and the lowest (0.666 ppm) in Ulva fasciata.